Rough weather ahead for Walter the farting dog - Kotzwinkle, William; Murray, Glenn; Colman, Audrey (New York : Puffin Books, 2007)
When an expert on animal gas tries to cure Walter, his farts keep building up until he floats away and is blown by the wind to a distant place, where he once again proves himself a hero.
Accelerated Reader AR
Keywords: Dogs -- Fiction; Flatulence -- Fiction